PROPORTION OF EARLY ANTENATAL CARE BOOKING AND ASSOCIATED FACTORS IN MEKELLE CITY, PUBLIC HEALTH INSTITUTIONS, NORTHERN ETHIOPIA, 2015 - Gidey, Gebreamlak; Abraha, Desta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to assess the proportion and associated factors for early initiation of antenatal care visit in Mekelle City, Tigray, Northern Ethiopia, 2015. Method: An institution-based cross-sectional study was employed among 391 pregnant women's in Mekelle special zone. A systematic sampling technique was used to select study participants. Pretested structured questionnaire was used to collect the data through interview. Data were entered into EPI info version 7 and analyzed using SPSS version 20, respectively. Bivariate and multivariate logistic regression was done to see significant variables with p<0.05 at 95% confidence interval (CI). Result: The proportion of pregnant women who initiate early antenatal care (ANC) visit was found to be 41.1%. Perceived correct time of initiation before 4 months (adjusted odds ratio [AOR]=3.261, 95% CI 1.391â€“7.645) and correct time told by others before 4 months with (AOR=6.617, 95% CI 2.580, 16.971) were found to have statistically significant positive outcomes association with early initiation of antenatal care visit. Conclusion: The proportion of early ANC initiation in Mekelle is lower than the World Health Organization recommendation which is <16 weeks gestation. Therefore, providing information to the community, initiation counseling, and providing health education on the benefits early ANC is crucial to improving maternal, neonatal, and child health outcomes.